Recent advances in very high cycle fatigue behavior of metals and alloys—a review - Sharma, Ashutosh; Oh, Min Chul; Ahn, Byungmin (Metals, 2020)
We reviewed the research and developments in the field of fatigue failure, focusing on very-high cycle fatigue (VHCF) of metals, alloys, and steels. We also discussed ultrasonic fatigue testing, historical relevance, major testing principles, and equipment. The VHCF behavior of Al, Mg, Ni, Ti, and various types of steels were analyzed. Furthermore, we highlighted the major defects, crack initiation sites, fatigue models, and simulation studies to understand the crack development in VHCF regimes. Finally, we reviewed the details regarding various issues and challenges in the field of VHCF for engineering metals and identified future directions in this area.
Keywords: Fatigue; Fish eye; Fracture; High-entropy alloy; Powder metallurgy; Very-high cycle